Transcriptomic and small RNA response to Mayaro virus infection in Anopheles stephensi mosquitoes. - Cory Henderson; Marco Brustolin; Shivanand Hegde; Gargi Dayama; Nelson Lau; Grant L Hughes; Christina Bergey; Jason L Rasgon (Public Library of Science (PLoS), 2022)
Mayaro virus (MAYV) is an arboviral pathogen in the genus Alphavirus that is circulating in South America with potential to spread to naïve regions. MAYV is also one of the few viruses with the ability to be transmitted by mosquitoes in the genus Anopheles, as well as the typical arboviral transmitting mosquitoes in the genus Aedes. Few studies have investigated the infection response of Anopheles mosquitoes. In this study we detail the transcriptomic and small RNA responses of An. stephensi to infection with MAYV via infectious bloodmeal at 2, 7, and 14 days post infection (dpi). 487 unique transcripts were significantly regulated, 78 putative novel miRNAs were identified, and an siRNA response is observed targeting the MAYV genome. Gene ontology analysis of transcripts regulated at each timepoint shows a number of proteases regulated at 2 and 7 dpi, potentially representative of Toll or melanization pathway activation, and repression of pathways related to autophagy and apoptosis at 14 dpi. These findings provide a basic understanding of the infection response of An. stephensi to MAYV and help to identify host factors which might be useful to target to inhibit viral replication in Anopheles mosquitoes.